If you don’t trust judges, let the scholars decide: The primacy of the Malaysian shariah advisory council on Islamic finance - Shuaib, Farid Sufian (Ankara Yildirim Beyazit University, 2017)
Malaysia adopts the principle of separation of powers where the function of the legislature is to enact laws, the executive to govern in accordance with the law and the court to decide disputes and to apply the law. It is an aberration when the law provides that a court of law has to revert to a body of scholars in determining what the law in deciding disputes between parties is. However, this occurs in Malaysia in the area of Islamic finance where the law establishes a Shariah Advisory Council consisting of scholar of Islamic finance under the auspices of the Malaysian Central Bank. The decision of the Shariah Advisory Council is final and binding upon any arbitration bodies and courts. This paper adopts a doctrinal analysis approach in examining this issue from the perspective of the constitution and the legal system, and seeks to reconcile this aberration with the reality of the practice of law and the practice of Islamic finance in Malaysia. The paper then examines alternative to this mechanism.